Research on SSB 1+X beam technology of 5G network - Bei LI; Yuhua HU; Xinyan WANG; Guoping XU; Guanghai LIU; Tian XIAO; Chen CHENG; Yi LI (Dianxin kexue)
Beam scanning and spatial dimensions in 5G was introduced in the 3GPP standard.When UE connects gNodeB, gNodeB uses SSB beam rotation to detect the optimal beam of UE.After UE was connected, the CSI-RS configuration information could be obtained and the CSI could be normal feedback，gNodeB adopted the optimal beam transmitted by the CSI-RS beam in turn.5G antennas flexibly configure the number of beams and take into account coverage in both horizontal and vertical dimensions.The development of broadcast beams and the horizontal 7 beams facing challenges were presented, the horizontal 7 beam and 1+X beam schemes were analyzed.Finally, efficiency was presented.